2020
DOI: 10.3390/cancers12113115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of the TERT Gene, Telomere Length, and Circulating TERT as Prognostic Markers in Rectal Cancer Patients

Abstract: Single-nucleotide polymorphisms (SNPs) in the TERT gene can affect telomere length and TERT expression and have been associated with risk and/or outcome for several tumors, but very few data are available about their impact on rectal cancer. Eight SNPs (rs2736108, rs2735940, rs2736098, rs2736100, rs35241335, rs11742908, rs2736122 and rs2853690), mapping in regulatory and coding regions of the TERT gene, were studied in 194 rectal cancer patients to evaluate their association with constitutive telomere length, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Importantly, several studies have been demonstrated that circulating TERT mRNA is an independent prognostic marker in different types of tumors ( 35 ), including gastric ( 48 ), prostatic ( 49 ), lung ( 50 ), and colorectal cancers ( 38 , 46 , 51 ). In addition, TERT mRNA levels in plasma samples of patients with rectal cancer were identified as a predictive marker of response to therapy ( 38 , 39 , 51 ). In the present study, we found that patients of the T cohort showed significantly higher levels of circulating TERT mRNA than those of the NT cohort both at baseline and follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, several studies have been demonstrated that circulating TERT mRNA is an independent prognostic marker in different types of tumors ( 35 ), including gastric ( 48 ), prostatic ( 49 ), lung ( 50 ), and colorectal cancers ( 38 , 46 , 51 ). In addition, TERT mRNA levels in plasma samples of patients with rectal cancer were identified as a predictive marker of response to therapy ( 38 , 39 , 51 ). In the present study, we found that patients of the T cohort showed significantly higher levels of circulating TERT mRNA than those of the NT cohort both at baseline and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from plasma samples as previously described ( 38 , 39 ), using 1 mL instead of 500 μL of plasma and reagents’ quantities adjusted accordingly. RNA was reverse transcribed into cDNA using the SuperScript TM III RNase reverse transcriptase assay (Thermo Fisher Scientific) in a final volume of 80 μL, according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from PBMC, using QIAmp DNA Blood Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer’s instructions. Relative telomere length (RTL) was determined by monochrome quantitative multiplex real-time PCR, as previously described ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…The TG genotype was more likely to result in complete response (CR) (p = 0.02). Rampazzo et al [33] analysed 8 SNPs (rs11742908, rs2736108, rs2736098, rs2736100, rs2736122, rs2735940, rs2853690 and rs35241335) located in the regulatory and coding regions of the telomerase reverse transcriptase (TERT) gene. Their results showed the rs2853690AA/GG and rs2736108CC genotypes were associated with less telomere erosion and lower levels of circulating TERT following nCRT.…”
Section: Single-nucleotide Polymorphisms (Snps)mentioning
confidence: 99%